Računalniško obvladovanje kakovosti v avtomobilski industriji - Metljak, Drago (Strojniški vestnik, 2001)
We present a computer-supported system for monitoring and quality control in a supply chain in the automotive industry. A standardized general model of a factory revealing the structure of the important business and manufacture functions, including functions of the CAQ (computer-aided quality) system, is defined. Within the model there is an emphasis on(1) the measurement and control of process and products, and(2) the management of nonconformities and systematic corrective and preventive action and continual improvement. For illustration, two case studies of successful CAQ-system implementations are demonstrated.
Keywords: obvladovanje kakovosti; CAQ; zasledovanje proizvodnje; QS9000; automotive industry; avtomobilska industrija; organizacija dela; kvaliteta; proizvodnja